Organic and Microbial Biomass Carbon Contents ofAggregates in a Toposequence of Pasture Soils - Asskin, Tayfun; Kizilkaya, Ridvan (Asian Journal of Chemistry, 2010)
The objective of this study was to determine changes in microbial biomass carbon (Cmic) and organic carbon (Corg) of soil aggregates along a pasture slope. Soil samples from 0–50 mm depth were taken from three landscape positions (shoulder, backslope and footslope) of a pasture in Samsun, Turkey. For each landscape position, soil aggregates were separated into eight aggregate size classes using a dry sieving method and then Corg was analyzed. At all positions, macroaggregates (especially 841–1190 and 1190–1680 μm in sizes) were higher than microaggregates. The contents of Corg varied between 0.65 and 2.08%. The highest Corg contents were found in footslope position and the lowest contents in backslope. All properties are higher at footslope position than the other positions. Generally, Cmic was greater in microaggregates of <250 μm, in macroaggregates of 250–420, 420–841, 841–1190 μm than in the other aggregate size at all positions, whereas Corg : Cmic was higher in macroaggregates of 1190–1680, 1680–2380, 2380–4760 μm than the other macro and microaggregate size. Consequently, in macroaggregates especially this class is relatively more Corg than the microaggregates, even if the absolute values of Cmic were lower.